Eslicarbazepine acetate is porphyrogenic and should be used with caution in patients with the acute hepatic porphyrias - Ma, Christopher D.; Bonkovsky, Herbert L. (Frontiers in Pharmacology, 2022)
Eslicarbazepine acetate, a third-generation antiepileptic drug (AED), has shown improved clinical response and safety in comparison to older generation AEDs for patients with partial-onset seizures. It is currently not known whether eslicarbazepine acetate is safe to use in patients with the acute hepatic porphyrias (AHPs) since a few first-generation AEDs, such as phenobarbital and carbamazepine, are known porphyrogenic agents. In this study, we used a recently published in vitro fluorescence-based screening assay to screen for porphyrogenicity in various agents. The assay confirmed that among the tested compounds used, allyl isopropyl acetamide, carbamazepine, eslicarbazepine, and phenobarbital were porphyrogenic. Thus, eslicarbazepine acetate should be avoided if possible in patients with the AHPs, but if initiated, patients should be closely monitored and the drug should be discontinued if a porphyric exacerbation occurs.